"Just Published": Advertising Books of Instruction, Misfortune, South Sea Affairs, and Entertainment in The Post Boy (1721). Issue 7 (3rd October 2021) - Brownlees, Nicholas
ABSTRACT: One of the most important English newspapers in 1721 was The Post Boy . Printed in London, it sold well in the capital and many copies were also sent out to its country subscribers. However, like all successful newspapers of the time, its financial solidity was not just based on sold copies but on its advertising. This essay examines the substantial number of book advertisements in six issues of The Post Boy in 1721. The research develops previous work on eighteenth-century book advertising by focusing on a particular newspaper in a single year and in relation to specific categories of book advertisements. The content analysis explores the target readers' interests and apparent reasons for purchasing the advertised works. The most advertised works were broadly instructive with few publications concerned with entertainment and leisure.